The Role of Work Discipline and Organizational Citizenship Behavior (OCB) on Police Job Satisfaction at the East Kalimantan Regional Police - Syafruddin Syafruddin; Muhammad Afifi Rahman (Transpublika Publisher, 2026)
Job satisfaction is one of the important factors in improving individual performance and organisational effectiveness, including in law enforcement institutions such as the Indonesian National Police. In a police organisational environment that demands high professionalism, work discipline and Organisational Citizenship Behaviour (OCB) are seen as factors that can influence the level of job satisfaction among members. Notwithstanding their presumed relevance, empirical inquiries addressing the role of these two determinants in shaping the job satisfaction of personnel within the East Kalimantan Regional Police remain comparatively sparse. In response to this lacuna, the present study endeavors to examine the extent to which work discipline and Organizational Citizenship Behaviour (OCB) contribute to the job satisfaction of members of the East Kalimantan Regional Police. This investigation employs a quantitative framework, utilizing multiple linear regression to evaluate data obtained from 413 police personnel. The dataset was compiled through a five-point Likert-scale questionnaire administered to respondents selected through random sampling procedures. The empirical results indicate that both work discipline and Organizational Citizenship Behaviour (OCB) exert a positive and statistically meaningful influence on the job satisfaction of personnel within the East Kalimantan Regional Police. Partially, both variables contribute significantly to increasing job satisfaction, and simultaneously, both are able to explain the variation in job satisfaction among members in the East Kalimantan Regional Police organisation. Thus, improving work discipline and strengthening OCB behaviour in the police environment can be an important strategy in increasing member job satisfaction and supporting overall organisational performance.